Bayesian deep learning for single-cell analysis. (December 2018) - Way, Gregory; Greene, Casey
A recent approach for single-cell RNA-sequencing data uses Bayesian deep learning to correct technical artifacts and enable accurate and multifaceted downstream analyses.